Analysis of Sales of Contraceptive Devices Before Covid-19 During the Pandemic and New Normal at PT. Bintang Semesta Farma Bandung - Neng Seni Nurhasanah; Yuni Megawati; Sa’ad Noor (Enrichment : Journal of Management, 2022)
In March 2020 covid-19 was found in Indonesia, one of the government's covid-19 countermeasures was PPKM (enforcement of restrictions on community activities) which caused most of the sales to decline from various sectors, one of which was the sale of contraceptives, PT. Bintang Semesta Farma Bandung which has decreased from 2019 to 2020 and has increased in the new normal period in 2020 to 2021. The research method used is a quantitative method, namely processing and manipulating raw data regarding useful information. In 2019 or before the Pandemic, total sales reached Rp. 6,883,809,682. During the Pandemic or in 2020, the total sales value decreased to Rp. 5,774,344,378 or decreased by 16%. Meanwhile, in 2021 or in the New Normal period, resale has increased and touched the figure of Rp. 9,679,671,921 or an increase of 68%.3. There is a strong and significant positive relationship between Sales of Contraceptive Devices and the Confirmed Number of Covid-19 (r0.674), sales of contraceptives increased in line with the increase in the number of confirmed Covid-19 in 2020